(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article investigates the communicative approach (CA) as a dominant paradigm in English as a Foreign Language (EFL) instruction. Drawing on both theoretical frameworks and empirical evidence, the study examines how communicative language teaching (CLT) principles are applied in real classroom contexts, the challenges teachers face in implementation, and the measurable outcomes for learners’ communicative competence. The findings suggest that while CLT significantly enhances students’ speaking fluency and interactive skills, its effectiveness depends heavily on contextual adaptation, teacher proficiency, and institutional support.